Fiber Compounds and Human Health - Camara, Montana; Fernandez-Ruiz, Virginia; Morales, Patricia; Cortes Sanchez-Mata, Maria (Current Pharmaceutical Design, 2017)
Background: It is known that insufficient consumption of fiber in Western societies is directly linked to certain diseases. The required daily fiber intake can be obtained from foods such as fruits and vegetables, whole grains, legumes, nuts and others, or by eating foods enriched with fiber as a functional ingredient. Objective: This review studies certain fiber compounds such as oligosaccharides (namely α-galactosides and fructans), arabinoxylans and β-glucans. Results: The European regulatory body governing nutrition and health claims aims to protect consumers' right to receive truthful information about food by verifying statements on
Keywords: β-glucans